2014
DOI: 10.5539/jel.v3n1p16
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Integrating Service Learning into Short-Term International Study

Abstract: "The best part of the trip was the community work…I would have liked to build more homes…lots of meaningful things were exchanged between us and the community members." Student Testimonials, La Gloria, Mexico (2009) AbstractIn an era of significant social, political, and economic globalization, it is crucial for health and human services educators to adopt a more hands on international view vis-à-vis student education. This article presents information that will assist educators in extending domestic service l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For example, in their respective studies, Stewart (2012) and Bowen (2010) found that the inclusion of a service-learning course increased students' professional skills and civic abilities and knowledge about community issues. Kovarik (2010) and more recently, Daly et al (2014) indicated that participation in service-learning courses provided wider learning opportunities for students. By participating in service-learning, students would come across different people and issues in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in their respective studies, Stewart (2012) and Bowen (2010) found that the inclusion of a service-learning course increased students' professional skills and civic abilities and knowledge about community issues. Kovarik (2010) and more recently, Daly et al (2014) indicated that participation in service-learning courses provided wider learning opportunities for students. By participating in service-learning, students would come across different people and issues in the community.…”
Section: Discussionmentioning
confidence: 99%
“…As the first step in developing the instrument, a vast amount of literature on outcomes of service-learning was reviewed (e.g., Ahmad, Said, Mansor, Mokhtar, & Ghani, 2014;Billig & Eyler, 2003;Bringle & Hatcher, 1995;Birdwell et al, 2013;Brown, 2015;Burns & Stokamer, 2011;Butin, 2010;Calvert & Kurji, 2012;Couse & Russo, 2006;Daly, Baker, & Williams, 2014;Daniel, 2013;Deba, Jabor, Buntat, & Musta'mal, 2014;Deba, Jabor, Sukri Saud, & Buntat, 2015;Deeley, 2010;Denby, 2008;Eyler & Giles, 1999;Eyler et al, 1997;Felten & Clayton, 2011;Ferrari & Chapman, 2014;Furco, 2010;Gershenson-Gates, 2012;Gerstenblatt & Gilbert, 2014;Greenman, 2014;Jacoby, 2003;Jacoby, 2013;Jerome, 2012;Lu & Lambright, 2010;O'Grady, 2014;Said, Ahmad, Hassan, & Awang, 2015;Said, Ahmad, Mansor, & Awang, 2015;Waterman, 2014). Afterwards important significant statements were collected, and out of these statements, three themes were extracted: content knowledge, interpersonal skills, and volunteering attitude.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…Our program builds on the developing literature measuring the impact of service-oriented off-campus programs on student growth (Daly et al, 2014; Jones, LePeau, & Robbins, 2013; Niehaus & Crain, 2013). However, it differs from short-term, service-based travel experiences for students, such as the alternative spring break model.…”
Section: Program Designmentioning
confidence: 99%
“…A second high-impact practice is off-campus study, which is often equated with studying abroad (Kuh, 2008). Although there are multiple benefits cited for studying abroad, including learning about cultural differences, Sobania and Braskamp (2009) introduced the term study away to emphasize that domestic off-campus study may also be a transformative learning experience for students (Daly, Baker, & Williams, 2014). Domestic "study away" allows students to "further their knowledge in their own communities" and provides them the opportunity to "open their minds, hearts, and behaviors to difference and .…”
mentioning
confidence: 99%